Opening up the black box: looking for a more capacious version of capacity in global health partnerships. Issue 3 (1st September 2016) - Wendland, Claire L.
Abstract: Some versions of capacity building construe the goal of North‒South partnerships as rendering African laboratories, doctors, scientists, and universities indistinguishable from their counterparts in wealthier nations. The specificities, histories, peculiarities, or inner workings of African institutions and individuals are black-boxed ‒ no one needs to know about them. This article draws on research at Malawi's College of Medicine and the work of other social scientists and historians to sketch out a more capacious model of capacity, one in which capacity building is grounded in specificity, attends to material difference, is flexible and innovative, and involves as much learning as teaching. This model of capacity building requires consideration of areas in which the Northern partners in "global health" can be brought to the level of their colleagues in Africa.